1994
DOI: 10.1007/bf01707671
|View full text |Cite
|
Sign up to set email alerts
|

Death by tanning — a case of fatal basic chromium sulphate poisoning

Abstract: A woman ingested 400 ml of leather tanning solution containing 48 g of basic chromium sulphate (CrOHSO4). This substance forms hydrogen ions and trivalent chromium when it reacts with tissue proteins. The patient died of cardiogenic shock, complicated by pancreatitis and gut mucosal necrosis and haemorrhage. There are no reported cases of toxicity due to oral ingestion of trivalent chromium. Toxicity of hexavalent and trivalent chromium is discussed and suggestions made for management of future cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A 41-year-old woman, who ingested 48 g chromium sulfate, developed a hemorrhagic gastroenteritis, pancreatitis, and intractable cardiogenic shock. 11 Postmortem examination demonstrated an erosive gastroenteritis of the entire gut, hemorrhagic pancreatitis, pulmonary congestion, and peritonitis.…”
Section: Trivalent Chromiummentioning
confidence: 99%
“…A 41-year-old woman, who ingested 48 g chromium sulfate, developed a hemorrhagic gastroenteritis, pancreatitis, and intractable cardiogenic shock. 11 Postmortem examination demonstrated an erosive gastroenteritis of the entire gut, hemorrhagic pancreatitis, pulmonary congestion, and peritonitis.…”
Section: Trivalent Chromiummentioning
confidence: 99%
“…However, there have been some cases reporting its dangerous side-effects such as acute hepatitis, thrombocytopenia, and renal failure. [111213] Green tea, which is widely used because of its ant-oxidant, weight-reducing and anti-cancer properties, contains Camellia Sinensis. There have been several cases that show an association of Camellia Sinensis with liver toxicity ranging from acute hepatitis to liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of available RCTs concluded that weight reduction with chromium although statistically significant was not clinically meaningful [2] . There have been case reports of chromium toxicity causing acute hepatitis, thrombocytopenia and renal failure due to both environmental [16,17] and dietary supplements [18] . Although renal failure requiring dialysis is a more common concern [19] , those presenting with liver toxicity frequently elaborate aminotransferase elevations greater than 1000 mg/dL.…”
Section: Discussionmentioning
confidence: 99%